P113 An Exploration of Factors that Affect Perceived Onset Latency during the MSLT Test. (7th October 2021) - Puglia, M; Turton, A; Stonehouse, J; Rossely, A; Grbic, A; Packer, K; Stupar, D; Lemarrec, J; Howes, J; Hamilton, G
Abstract: It is assumed that during the MSLT test, the sleep laboratory environment will be appropriately resourced to facilitate sleep. However, anecdotal evidence suggests that a variety of factors may actually hinder sleep onset, although this possibility has not been formally investigated in the literature. Thirty-four MSLT participants, who attended the sleep unit between 2018 and 2019, completed a questionnaire that was designed to test perception of sleep onset latency by asking them how easy/difficult it was for them to fall asleep on 17 items that came from four categories. The four categories were the 1. sleep unit environment, e.g. noise/ room temperature; 2. the MSLT procedure, e.g. wires/fixed nap times; 3. the MSLT staff e.g. manner/ clarity of explanations and 4. pain/distress unrelated to the test. All items were rated on a five-point Likert scale. Space was provided for written comments for each category. Overall, the relationship with staff had the greatest impact on perceived sleep onset latency. Forty-one percent of participants reported that the provision of a thorough explanation of the day's procedure helped them fall asleep in naps. Thirty-five percent reported that their own pain and discomfort affected their ability to sleep. Light and noise had little impact. This research indicates that the staff-patient relationship plays a significant role in patient's experience of the MSLT and may potentially affect test outcomes.